2019
DOI: 10.1039/c9ra09705h
|View full text |Cite
|
Sign up to set email alerts
|

Well-dispersed Pd nanoparticles on porous ZnO nanoplates via surface ion exchange for chlorobenzene-selective sensor

Abstract: Well-dispersed and size-controlled Pd nanocatalysts were deposited on porous ZnO nanoplates via surface ion exchange for enhanced and selective chlorobenzene-sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…26 In the recent years, few research studies based on semi-conductive metal oxides have been reported for the reliable detection of CBZs. As reported previously, Pt-decorated ZnO NCs, 27 Au-decorated ZnFe 2 O 4 yolk-shell spheres, 28 In 2 O 3 nano-rods, 29 Pd NPs on porous ZnO nano-plates, 30 and coral-like SnO 2 nanostructures 31 have been reported as efficient sensing mediators for the reliable detection of CBZs. Besides this, FeO/CdO nanocubes and MCM-41 material-decorated GCEs have performed potentially to detect CBZs in an electrochemical approach.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…26 In the recent years, few research studies based on semi-conductive metal oxides have been reported for the reliable detection of CBZs. As reported previously, Pt-decorated ZnO NCs, 27 Au-decorated ZnFe 2 O 4 yolk-shell spheres, 28 In 2 O 3 nano-rods, 29 Pd NPs on porous ZnO nano-plates, 30 and coral-like SnO 2 nanostructures 31 have been reported as efficient sensing mediators for the reliable detection of CBZs. Besides this, FeO/CdO nanocubes and MCM-41 material-decorated GCEs have performed potentially to detect CBZs in an electrochemical approach.…”
Section: Introductionsupporting
confidence: 61%
“…The oxygen adsorption and the electrochemical CBZ oxidation were further conrmed by the preceding authors. 30,96,97 The enhanced sensing mechanism of the ternary RuO 2 /ZnO/ TiO 2 NC-based EC sensor could be explained using the band theory of semiconductor metal oxides. First of all, the capture of electrons in the conduction band of both TiO 2 and ZnO by adsorbed oxygen led to the development of an electrondepleted, space-charge layer at the interface of ternary RuO 2 / ZnO/TiO 2 NCs.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…Some bands have disbanded, while others shifted or transformed. However, the existence of Pb-O and Cd-O stretching vibrations resulted in the appearance of additional absorption peaks at 422 cm−1 [46][47][48][49]. Adsorption was confirmed by such changes in the FT-IR spectra.…”
Section: Ft-ir Analysis Of Zno Nanospheresmentioning
confidence: 90%
“…The smaller metallic particle size and better dispersion of the active centers have usually been related to a better overall catalytic activity for the HDC of different chlorinated hydrocarbons [11,31,47,48,50,57,60,81,88,90,91,118,119], though overly small particles have been suggested to have limited activity for some systems [88,120], since they may not be completely reduced before the reaction [88]. In contrast, most of the studies report an increase in activity per catalytic center, known as intrinsic activity or turnover frequency (TOF), when increasing the metal particle size, for the HDC of chloromethanes [21,23,24,32,49,121,122], indicating that the reaction is sensitive to the structure.…”
Section: Metallic Particle Size and Dispersionmentioning
confidence: 99%